Quantum mechanical investigation of the influence of the local environment on the vibrational properties of hydrogenated Si(111) - Juarez, Maria Fernanda (2009)
Periodic density functional calculations were performed to investigate the vibrational properties of hydrogenated and grafted Si(111) surfaces as a function of surface coverage and subsurface oxidation. Surfaces terminated with - CH3, - CCH, and - Cl groups were considered. Subsurface oxidation was taken into account by oxidizing one, two, and three silicon back bonds. The effect of anharmonicity was considered in the calculation of the stretching frequencies of the Si - H and C - H groups. The effect of the different adsorbates on the polarization of the electron density of the SiH group and on the electronic structure of the surface was investigated by means of electron density difference and density of states analyses. The Si - H stretching frequency increases with the surface coverage of - CCH and - Cl species, and it decreases with the increase in the surface coverage of - CH3. Positive (negative) frequency shifts correlate with the increase (decrease) of electron density along the Si - H bond. The Si - H stretching frequency shows a very good correlation with the Si - H bond length for all the systems investigated. The Si - C, C - H, and Si - Cl stretching frequencies increase linearly with the surface coverage of the - CH3, - CCH, and - Cl groups. The back-bond oxidation of a SiH group produces an increase in its stretching frequency and a decrease of the stretching frequency of the surrounding unoxidized SiH groups. All the calculated frequencies show very good agreement with the experimental values.